An integrated model for supplier selection using fuzzy analytical hierarchy process: a steel plant case study. (4th June 2010) - Gnanasekaran, Sasikumar; Velappan, Selladurai; Manimaran, P.
Supplier selection is one of the most important functions to be performed by the purchasing department. The supplier selection is a multi-criteria decision making (MCDM) problem involving both qualitative and quantitative criteria. In order to select the best suppliers, it is necessary to make a trade off between tangible and intangible criteria that conflict with each other. Today's globally competitive business environment warrants suppliers to supply raw materials punctually in the right quantity and quality. Manufacturers are increasingly concerned about supplier selection since reliable suppliers enable them to reduce inventory costs and improve product quality. This paper proposes an integrated model based on fuzzy analytical hierarchy process (AHP) for supplier selection. A decision support system (DSS) has been developed using Visual Basic and MS Access. The case study was conducted in a leading steel plant to demonstrate the application of the proposed model.